Four New Species of the Amblyoponine Ant Genus Amblyopone (Hymenoptera: Formicidae) from Southwestern China with a Key to the Known Asian Species - Xu, Zheng-Hui (Sociobiology, 2014)
Four new species of the amblyoponine ant genus Amblyopone Erichson, 1842 collected from southwestern China are described, i.e. A. kangba sp. nov., A. zoma sp. nov., A. meiliana sp. nov., and A. awa sp. nov. The queen caste of A. awa sp. nov. is reported. Measurements are supplemented to A. octodentata Xu based on the newly collected specimens. A key to the 29 known Asian species of the genus is provided based on the worker caste. Illustrations are provided for each species except for A. quadrata (Karavaiev).